Experiences and Perceptions of Older Adults with Lower-Risk Hormone Receptor-Positive Breast Cancer about Adjuvant Radiotherapy and Endocrine Therapy: A Patient Survey - Marie-France Savard; Mashari Jemaan Alzahrani; Deanna Saunders; Lynn Chang; Angel Arnaout; Terry L. Ng; Muriel Brackstone; Lisa Vandermeer; Tina Hsu; Ari Ali Awan; Katherine Cole; Gail Larocque; et al. (Current Oncology, 2021)
Older patients with lower-risk hormone receptor-positive (HR+) breast cancer are frequently offered both radiotherapy (RT) and endocrine therapy (ET) after breast-conserving surgery (BCS). A survey was performed to assess older patients’ experiences and perceptions regarding RT and ET, and participation interest in de-escalation trials. Of the 130 patients approached, 102 eligible patients completed the survey (response rate 78%). The median age of respondents was 74 (interquartile range 71–76). Most participants (71%, 72/102) received both RT and ET. Patients felt the role of RT and ET, respectively, was to: reduce ipsilateral tumor recurrence (91%, 90/99 and 62%, 61/99) and improve survival (56%, 55/99 and 49%, 49/99). More patients had significant concerns regarding ET (66%, 65/99) than RT (39%, 37/95). When asked which treatment had the most negative effect on their quality of life, the results showed: ET (35%, 25/72), RT (14%, 10/72) or both (8%, 6/72). Participants would rather receive RT (57%, 41/72) than ET (43%, 31/72). Forty-four percent (44/100) of respondents were either, “not comfortable” or “not interested” in participating in potential de-escalation trials. Although most of the adjuvant therapy de-escalation trials evaluate the omission of RT, de-escalation studies of ET are warranted and patient centered.